Identifying Batik Motifs in Early Childhood Art Learning: Developing Creativity and Cultural Awareness - Afwanni, Tiwi; Pamungkas, Joko (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
Batik is one of Indonesia's most renowned traditional art forms, crafted by hand and rich in cultural significance. Introducing batik to children early is essential for preserving local heritage and fostering creativity, imagination, and motor skill development. This study aims to explore the identification of batik motifs in art education at PPBI Batik Kindergarten Yogyakarta and its role in enhancing creativity and cultural awareness in early childhood. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The research subjects included the principal and teachers of the kindergarten. Data analysis involved reduction, presentation, and conclusion drawing. The findings revealed that several traditional batik motifs are incorporated into art learning, including kawung, parang, lereng (slope), truntum, and semen motifs, alongside modernized variations created by the children. The study demonstrated that identifying and learning batik motifs enhanced children’s artistic skills and deepened their cultural awareness. Through the use of visual and qualitative analysis methods, children were able to understand and appreciate the symbolic meanings of various motifs. Their participation in the creative process—from motif introduction, drawing, and canting to coloring—enhanced their creativity and art skills. This research concludes that art education involving batik at PPBI Batik Kindergarten Yogyakarta fosters children’s creativity, artistic abilities, and cultural awareness while contributing to the broader preservation of Indonesia's cultural heritage.